Methods and means of laser layer Jones matrix mapping of polycrystalline films of biological fluids - Ushenko, Olexander; Soltys, Iryna; Dubolazov, Olexander; Pavlov, Sergii; Garasym, Vasyl; Kolomiiets, Alona; Yeraliyeva, Bakhyt (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
The results of the theoretical substantiation and experimental validation of a novel laser polarization-interference method for Jones matrix mapping with digital phase layer-by-layer scanning of the object field of polycrystalline bile films are presented. Statistical analysis of the layer-by-layer maps of the real and imaginary components of the Jones matrix images has revealed a set of diagnostic markers – skewness and kurtosis – sensitive to variations in the linear and circular birefringence of the polycrystalline structure within the supramolecular networks of dehydrated bile films.